Revealing the unexpected promotion effect of diverse potassium precursors on α-MnO2 for the catalytic destruction of toluene. Issue 7 (9th March 2020) - Zhu, Qing; Jiang, Zeyu; Ma, Mudi; He, Chi; Yu, Yanke; Liu, Xiaohe; Albilali, Reem
Abstract : The alkali metal potassium has the functions of structure promotion and electronic modulation in metal oxides. Abstract : The alkali metal potassium has the functions of structure promotion and electronic modulation in metal oxides. Herein, diverse potassium precursors (KOH, KNO3, K2 SO4, and KCl) were introduced to α-MnO2 nanorods through a facile post-processing strategy. The presence of potassium species has a remarkable promotion effect on the catalytic performance of α-MnO2 . Amongst them, the KOH/MnO2 sample has the highest activity and can destroy 90% toluene (1000 ppm) at just 226 °C with a reaction rate of 3.39 × 10 −4 mol gcat −1 s −1, which is over 20 times higher than that of pure α-MnO2 . Different anions in the potassium precursors bring a distinct mutation in the α-MnO2 structure, promote the formation of MnO6 –K–MnO6 bridging bonds in α-MnO2, and exhibit obvious diverse abilities for balancing charge transfer. KOH is identified as the most promising precursor for alkali metal modification, which significantly improves the distribution of K species over the α-MnO2 surface and strengthens the content and activity of lattice oxygen. It is confirmed that the lattice oxygen plays a key role in the catalytic oxidation of toluene over α-MnO2, which follows the Mars–van Krevelen mechanism. Positive hole defects (Mn 3+ ) caused by KOH treatment play an important role in the diffusion of O and enhance the reducibility of manganese oxide. In addition, the enhanced specific surface area, pore volume, and surface acidity are also conducive for the catalytic oxidation of toluene.